Use of Telemedicine in Evaluation of Pediatric Surgical Patients in COVID-19 Time - Rai, Rahul Kumar; Pandey, Anand; Gupta, Archika; Singh, Gurmeet; Rawat, Jiledar (Annals of the National Academy of Medical Sciences (India), 2022)
Objective The word “telemedicine” literally translates to “healing at a distance.” In the current scenario of the coronavirus disease 2019 (COVID-19) pandemic and shut outpatient department, the patients are facing difficulty in consultation. This article evaluated the use of telemedicine in the management of pediatric surgical patients.Materials and Methods In this observational cohort study, from April 2020 to August 2020, all patients who took advice on phone/WhatsApp were assessed for addressing their complaints. The data was collected and analyzed.Result A total of 307 patients were provided consultation via telecommunication. The male to female ratio was 2.3:1. Fifty-six (18.2%) patients called on an emergency basis, while the remaining 251 (81.8%) patients called for nonemergency or routine problems. Of these, attendants of 25 (8.14%) patients were not able to state the situation adequately. They were called to the department. Of these, 11 (3.5% of total) patients were admitted. One-hundred and eighty-three (59.6%) patients were in the department's follow-up, while the remaining 124 (40.4%) were new patients. The attendants of 296 (96.4%) patients were satisfied by using this modality of consultation.Conclusion In the current scenario, telecommunication may help us to avoid unnecessary travel to the hospital. It may be helpful to deal with minor clinical complaints and evaluating for an emergency.
Keywords: COVID-19; telemedicine; pediatric surgery; teleconsultation